2020
DOI: 10.1007/s00261-020-02700-6
|View full text |Cite
|
Sign up to set email alerts
|

Validation of computed tomography angiography using mean arterial pressure gradient as a reference in stented superior mesenteric artery

Abstract: Purpose The aim of this prospective study was to validate the diagnostic performance of computed tomography angiography (CTA) in endoprosthesis stenosis in the superior mesenteric artery (SMA) using mean arterial pressure (MAP) gradients during angiography as a reference method. Methods Twenty-nine patients with mesenteric atherosclerotic disease underwent 45 paired measurements of endoprosthesis stenosis in the SMA with CTA and MAP gradients betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Images were analyzed by two radiologists, with any disagreement resolved by consensus or with the help of a third senior radiologist. Interrater variability for superior mesenteric artery (SMA) stenosis assessment has been evaluated previously (7). Data were prospectively collected in a dedicated file.…”
Section: Ct Image Acquisition and Analysismentioning
confidence: 99%
“…Images were analyzed by two radiologists, with any disagreement resolved by consensus or with the help of a third senior radiologist. Interrater variability for superior mesenteric artery (SMA) stenosis assessment has been evaluated previously (7). Data were prospectively collected in a dedicated file.…”
Section: Ct Image Acquisition and Analysismentioning
confidence: 99%
“…Intra-arterial pressure measurements are performed proximal and distal to a stenosis. This is considered to be the most accurate method in diagnosing a significant SMA lesion (47). A 10 mmHg pressure gradient across a SMA stenosis is deemed significant (3).…”
Section: Angiographymentioning
confidence: 99%
“…However, the finding of a significant stenosis on DUS should, based on this study, be regarded as a true stenosis and has the advantage of being non-invasive in contrast to a conventional digital subtraction angiography (DSA), and without radiation, in contrast to CTA and DSA. Grading of endoprosthesis stenosis with CTA after SMA stenting had a sensitivity and specificity of 52.4% and 87.5%, respectively, in a recent study using trans-stenotic mean arterial pressure (MAP) gradient as a reference (47).…”
Section: Post-treatment Follow-upmentioning
confidence: 99%
“…The CMI patients must be followed since the reported incidence of restenosis of the endoprosthesis is as high as 33%, and the mortality after acute occlusion of the stent be 50%. 13–15 The guidelines recommend a transabdominal duplex ultrasound (TA-DUS) as an adjunct to the initial investigation of the patients with CMI as well as for the follow-up. 3 , 4 , 16 , 17 Validation studies in the 1990s compared duplex ultrasound (DUS) flow velocities with digital subtraction angiography (DSA)-verified stenosis of the mesenteric arteries, and a wide range of cut-offs for velocities was reported and used in the different DUS criteria for significant mesenteric artery stenoses.…”
Section: Introductionmentioning
confidence: 99%
“…DUS is operator-dependent, and the visualization of the mesenteric arteries can be challenging in some patients. 13 , 14 , 18 Furthermore, it has been reported that the patients after revascularization and particularly after stenting of the mesenteric arteries, can still have persistently higher peak systolic velocity (PSV) beyond 335 cm/s despite asymptomatic angiographic stenosis of <20% of the stented superior mesenteric artery (SMA). 19 …”
Section: Introductionmentioning
confidence: 99%